PENEGAKAN HUKUM TINDAK PIDANA PEMBAJAKAN PERANGKAT LUNAK KOMPUTER OLEH KEPOLISIAN RESOR KOTA PEKANBARU - Dicky Wirian Lafari; Erdianto '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Computer software piracy is any form of reproduction or use of the softwarewithout a license or outside of what has been regulated by the Law on Copyright andlicensing agreements. The purpose of this study, first to determine the crime of piracylaw enforcement computer software, Second, to know the police barriers in lawenforcement criminal acts of piracy of computer software and, third, to know theeffort Police carried out to overcome obstacles in law enforcement criminal offenseof computer software piracy by Keplisian Resor Kota Pekanbaru.There are threemain issues that can be inferred. First, law enforcement against criminal acts ofpiracy of computer software for not running optimally the presence of obstacles,Second, obstacles encountered in law enforcement software piracy offenses is in theform of internal factors, Third, efforts to overcome this obstacle is to revise Law No.19 of 2002 on Copyright and increase the knowledge of the police in the field ofinformation and technolgi. Suggestions author, first, is expected to police in carryingout the crime of piracy law enforcement computer software should not merelyrepressive but also preventive socialiszation manner. Second, the police shouldimprove their knowledge in the field of information and technology and increasepersonnel investigators in solving the crime of piracy of computer software. Third, tothe whole society in order to begin to appreciate the creative works of others to buyan original computer program is not being pirated.Keywords: Law Enforcement-Crime-Piracy Computer Software